KASHF AS COMPLEMENTARY EPISTEMOLOGY: REASSESSING AL-GHAZĀLĪ IN ISLAMIC PHILOSOPHY OF SCIENCE - Muhdi Ali; Awan Farih; Suadi Sa’ad; Masykur Masykur (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2026)
This study discusses the tendency of contemporary scholarship to reduce kashf to merely an intuitive or psychological experience, thereby overlooking its epistemological significance in Islamic philosophy of science. Its aim is to critically reassess the position of kashf in al-Ghazālī's epistemology and to construct a complementary epistemological framework related to modern scientific observation. This research employs a qualitative philosophical approach using Gadamerian hermeneutics, focusing on the interpretative analysis of al-Ghazālī's works, namely al-Munqidh min al-Ḍalāl and Iḥyā’ ‘Ulūm al-Dīn, and situating them in a dialogue with contemporary philosophy of science. The analysis involves three stages: text interpretation, epistemological comparison, and conceptual synthesis. Findings show that kashf in al-Ghazālī's framework functions not only as mystical intuition but also as a structured epistemic mode based on spiritual discipline, inner verification, and moral purification. This study indicates that kashf complements empirical observation by overcoming its limitations in accessing metaphysical dimensions, while maintaining its own criteria of internal validity. Based on this, the study formulates a complementary epistemological model consisting of three integrated domains: empirical (sensory observation), rational (intellectual reasoning), and intuitive-transcendental (kashf). This model provides a more comprehensive epistemological framework that allows dialogue between Islamic intellectual tradition and modern science, particularly in expanding the scope of valid knowledge beyond empirical reductionism.